IJCM_259A: Non-communicable disease (NCD) programme -factors influencing awareness and utilization of the services among adults of Madurai district, Tamil Nadu- a community based cross-sectional study. - Harini; Hemamalini B.; Priya S. (Wolters Kluwer Medknow Publications, 2024)
Background: Healthcare at people's doorstep called Makkalai Thedi Maruthuvam (MTM) scheme was launched by Tamil Nadu Government in 2021 to further improve the access to NCD care by ensuring door step blood sugar & blood pressure screening, drug delivery by designated trained manpower called Women Health Volunteers (WHV). Assessing the programme awareness and its utilization at this juncture is the need of the hour. Hence, the present study was conducted. Objectives: 1. To assess the awareness about MTM scheme among adults >30 years in the field practice area, Madurai district 2. To determine the factors influencing awareness and utilization of MTM services Methodology: A community based cross-sectional study was done among 165 adults of >30 years in field practice area of our department in October 2023. By cluster sampling, participants were interviewed using a pre-structured validated questionnaire containing socio-demographic details and data to assess awareness and factors influencing awareness and utilization of MTM services. Data were entered in MS Excel and analysed using SPSS. Results: Mean age was 54±13.60 years. 60% were females, 83% were literates,63% were employed.80% were aware about the scheme and 74% awareness was through healthcare workers,98% preferred door to door services. Awareness regarding lifestyle modifications, breast, cervix and oral cancer screening were 56%,40%,39% and 20% respectively. There is statistically significant association between MTM awareness and age, occupation, blood sugar and blood pressure check-up in the last one year. By multiple logistic regression, awareness among those 50 yrs. Those with awareness had 2.62 times odds of utilization of services as compared to those without awareness. Conclusion: There is a good awareness and utilization of MTM services. To sustain this, IEC activities can be done at regular intervals with special emphasis on cancer screening.